Predictors of proper inhaler technique and asthma control in pediatric patients with asthma. Issue 5 (26th January 2021) - Almomani, Basima A.; Al‐Qawasmeh, Batool S.; Al‐Shatnawi, Samah F.; Awad, Samah; Alzoubi, Sirin A.
Abstract: Background: Improper use of asthma inhalers is one of the potential factors of poor asthma control among children. This study aimed to assess the proper handling of asthma inhalers and asthma control in addition to factors influencing them among pediatric patients who self‐administer their inhalers. Methods: A cross‐sectional study was conducted in Jordan from February 2019 to February 2020. All eligible pediatric patients with asthma attending outpatient settings were approached. The inhalation technique was assessed according to a standard checklist, and asthma control was assessed using the Asthma Control Test. Results: A total of 150 patients were included in this study. A metered dose inhaler (MDI) was the most commonly used inhaler device (89.4%) which was used appropriately by only 13.4% of participants. Whereas, appropriate use of Turbohaler and Diskus was reported by 38.5% and 28.9%, respectively. The higher level of parental knowledge was associated with higher number of correct MDI steps (OR = 1.066; 95% CI = 1.010–1.125; p  = .020) and less reported errors in critical steps (OR = 0.949; 95% CI = 0.900–0.999; p  = .047). Higher level of both parental education and pediatric average stigma score (less stigmatized) were associated with better asthma control ([OR = 5.181; 95% CI = 1.238–21.677; p  = .024], [OR = 2.825; 95% CI = 1.420–5.619; p  = .003], respectively). Conclusion: Continuous education on appropriate inhaler self‐administration for asthmatic children is highly recommended. Clinical pharmacists play a major role toward improving the administration of inhalers through patient training and counseling.